Cross‐entropy method for distribution power systems reconfiguration. Issue 3 (29th October 2019) - Sebaa, Karim; Gelen, Ayetül; Nouri, Hassan
Abstract : Cross‐entropy (CE) is a powerful simulation method for the solution of continuous and combinatory optimization problems. The work presented here utilizes the CE method for the optimal topology of distribution power systems (DPSs). The optimal network switches are determined for the reduction of active power loss. The adapted CE method is tested on three case studies, namely, the 33‐node, 83‐node, and 880‐node DPSs. The results are compared with other reconfiguration algorithms to demonstrate the superiority of the proposed algorithm. The impact of the distributed generation is also investigated. The effective integration of the photovoltaic panels at midday, when their production is highest and meets the peak demand, is showed. Finally, the real‐time reconfiguration strategy based on the switching effort reduction is proposed and enhanced via an adequate selection of the initial switch states.